Effective Primer Selection for Differentiating Periplaneta Species via PCR - Hamad, Sara Salam; Khaled, Shifaa Waleed (Procedia of Engineering and Life Science, 2023)
This study utilized random polymerase chain reaction (PCR) with 10 random primers to differentiate between two insect species, Aegyptica Periplaneta and Periplaneta japonic. The results revealed a total of 29 bands, with 23 being polymorphic. The classification of the animal kingdom, especially insects, is complex due to the abundance and diversity of organisms. Traditional phenotypic methods often fall short in identifying closely related species, necessitating molecular approaches. Primers OP-A04, OP-A08, OP-B14, OP-B18, OP-C10, OP-C15, and OP-C18 showed the highest polymorphism (100%), while OP-A15 and OP-B09 had the lowest (40%). Primer OP-C06 exhibited no bands, indicating 0% polymorphism. Primers OP-A08 and OP-A15 had the highest efficiency (17.241%), whereas OP-C06, OP-C10, and OP-C15 had the lowest (3.448%). Notably, primer OP-A15 successfully discriminated between the species, while OP-C06 failed entirely. These findings underscore the importance of primer selection in molecular identification and suggest OP-A15 as a reliable primer for distinguishing between these Periplaneta species. Highlights: Primer OP-A15 effectively discriminated between Aegyptica Periplaneta and Periplaneta japonic. High polymorphism observed with primers OP-A04, OP-A08, OP-B14, OP-B18, OP-C10, OP-C15, and OP-C18. Primer OP-C06 showed 0% polymorphism and failed to differentiate between species. Keywords: Insect Classification, PCR, Random Primers, Species Differentiation, Periplaneta